LANGUAGE DIVERSITY BETWEEN TANGERANG COASTAL SOCIETY WITH PULAU SERIBU SOCIETY AS A FORM OF DIVERSITY IN INDONESIA - Hudaa, Syihaabul; Bahtiar, Ahmad; Nuryani, Nuryani (Universitas Hamzanwadi, 2021)
Language is synonymous with culture, accent and meaning in it. As a nation that has many languages, this is of course a complex problem. Differences in meaning in language can certainly hinder communication between one person and another. The purpose of writing this article is to discuss the differences in the language of the Tangerang coastal community and those in the Seribu Islands. The different language is certainly a sign of the diversity that occurs between the Tangerang coastal community and the Thousand Islands. Even though there are differences in language, they can still work together as a symbiotic mutualism. This research is classified into a descriptive qualitative type that describes the results of research using text in explaining the results of the research. Data collection techniques by taking notes, literature review, surveys, and interaction with the surrounding community. Based on research that has been conducted by researchers, there are language differences between the Tangerang coastal community and the people living in the Thousand Islands. This difference occurs because of the influence of their culture and ancestors.Keywords: language diversity; form of language; community culture